Enhancement of Software and Data Portability by Normalizing Variations in Hardware - Pon Rahul, M; Rishi Shree, S (International Journal of Computer Sciences and Engineering, 2025)
This paper explores the concept of software and user data portability by tackling device driver issues caused due to diversity in computer hardware. The objective of this paper is to implement a universal interface between the hardware and the software intended to minimize time and manpower. Drivers are required for software-hardware integration and different hardware manufactured by OEMs require device drivers designed specifically for the hardware component. Development of a new platform requires the software manufacturer to target a variety of hardware. Upgrading existing software requires the device drivers to be checked if they are compatible with the newer version of the software. Device drivers have to be written for each software platform separately. This results in a lot of time being consumed which directly affects the consumer such as delayed software and firmware updates, security patches, bug fixes etc. This interface addresses the driver development issues by providing a standard hardware platform for which the software can be developed.